Pembuatan Game Animasi Teka Teki Silang Menggunakan Adobe Flash CS6 - Jaria Rama Triyanti (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2022)
Computer technology is one of the technologies that can help accelerate human work. Computer technology has been applied in various fields including education, health, offices, telecommunications, business, military and so on, as well as in the world of entertainment. One form of entertainment including games, games are very rapidly developing along with advances in computer technology. Games are very much in demand both from children, adolescents to adults. The game itself is of various types, one of the games that enjoy doing and is educational for children and adolescents at the moment is a quiz-shaped game. Flash is a software that is generally used to make an animation, but currently flash is widely used for other things, for example making websites, games, etc. The purpose of this final project is to design animated games for children and people adults train their memory and outside insights about computers. Children and adults should never get bored with learning, thus helping children and adults learn about technology and make it easier for children and adults to learn general knowledge of technology and about computers. From the results of this study, it can be seen that the crossword animation game general knowledge about basic computer-based flash levels can find out more clearly about Adobe Flash CS6.